Masking release in cortical auditory evoked potentials with speech stimulus - Borges Rocha, Monyka Ferreira (2023)
Purpose: To analyze the effect of masking on the Cortical Auditory Evoked Potential with speech stimulus in young adults. Methods: Fourteen individuals aged between 19 and 28 years of both sexes with no hearing loss participated in the study. The Cortical Auditory Evoked Potential examination was performed with synthetic speech stimulus /ba/ simultaneous to Speech Shaped Noise presented under three conditions: steady noise with a 30 dB SPLep intensity (weak steady noise), steady noise with a 65 dB SPLep intensity o (strong steady noise) and modulated noise with 30 dB SPLep and 65 dB SPLep intensities at 25Hz and modulation period of 40 ms. Results: Higher latencies were observed in the cortical components, except P2, in the condition of strong steady noise and more meaningful measures of amplitude of the cortical components P1, N1 and P2 in the condition of modulated noise with statistically significant difference in comparison to the strong steady noise condition. There was worse wave morphology in the condition of strong steady noise, when compared to the other records. The average electrophysiological thresholds for the conditions of strong steady noise and modulated noise were 60 dB SPLep and 49 dB SPLep, respectively, showing a 11.7 dB mean difference. Conclusion: We could infer that there was a lower masking effect of modulated noise when compared to the strong steady noise condition, in the amplitude measurements of the cortical components and an average difference of 11.7 dB between the electrophysiological thresholds (interpreted as the measure of the Masking Release).